The Effects of High-Altitude Environment on Brain Function in a Seizure Model of Young-Aged Rats - Xie, Yao; Qin, Shenglan; Zhang, Rui; Wu, Hong; Sun, Guoyu; Liu, Lili; Hou, Xinlin (Frontiers in Pediatrics, 2020)
In this study, we examined the effects of high-altitude environment on the brain function of a seizure young-rat model. Two-hundred healthy, 3-week old, male rats were selected and equally divided into the plateau and plain groups. The plateau group was preconditioned in a simulated 5000-m altitude (barometric pressure [PB], 405 mmHg; partial pressure of oxygen [PO2], 84 mmHg) for 6 h/day for 7 days, while the plain group was kept in the ordinary atmospheric environment (PB, 760 mmHg; PO2, 157 mmHg) for 7 days. After preconditioning, rats were administered pentylenetetrazol (PTZ) to generate level-4 or stronger seizures. Electroencephalogram (EEG) signals were recorded (16 rats/group); the histology and apoptosis of hippocampal tissue were evaluated (6 rats/group); and spatial learning and memory were examined in the Morris water maze (12 rats/group; 6-weeks old). To induce a level 4 or stronger seizure successfully, a significantly higher PTZ dose was used in the plateau (81.32±21.57 mg/kg) than in the plain group (63.41±19.77 mg/kg, p<0.01); however, the plateau group survival rate was significantly lower than that of the plain group (26.2% vs. 42.9%, p<0.05). EEG parameters did not differ between the two groups. Histological analysis revealed that in the plateau group more dentate gyrus neurons (p<0.001) and less apoptotic cells (p=0.009) were observed compared to the plain group. No differences were found between the two groups in any of the parameters examined in the Morris water maze. Our results show that the disease outcome caused by low pressure and low oxygen environment in the plateau group was different to that in the plain group. The high drug dosage to induce seizures in the plateau group, accompanied by increased mortality rates after seizures, indicates that the seizure threshold may be higher in the plateau than in the plain group. Moreover, based on the histological findings, the plateau environment seems to exert a protective effect on brain development after seizures only for individuals with mild conditions